Integrated Photonic Devices: Robust and Broadband Optical Coupling by Topological Waveguide Arrays (Laser Photonics Rev. 14(2)/2020). Issue 2 (11th February 2020) - Song, Wange; Sun, Wenzhao; Chen, Chen; Song, Qinghai; Xiao, Shumin; Zhu, Shining; Li, Tao
Abstract : Topological designs boost progress in massive photonic integrations. In article number 1900193, Tao Li, Shumin Xiao, and co‐workers experimentally demonstrate a robust and broadband optical directional coupler and beam splitter using the coupling of edge states in a topological waveguide array. This work opens a new avenue towards topological devices with unique properties and functionalities and paves the way for future massive photonic integrations with loose fabrication requirement.